Oral findings in patients with Apert Syndrome Achados bucais em pacientes com Síndrome de Apert - Gisele da Silva Dalben; Lucimara Teixeira das Neves; Marcia Ribeiro Gomide (University of São Paulo, 2006)
INTRODUCTION: The Apert syndrome is a rare disorder of autosomal dominant inheritance caused by mutations in the FGFR2 gene at locus 10q26; patients with this syndrome present severe syndactyly, exophthalmia, ocular hypertelorism and hypoplastic midface with Class III malocclusion, besides systemic alterations. Most investigations available on the Apert syndrome address the genetic aspect or surgical management, with little emphasis on the oral aspects. OBJECTIVE: to investigate the oral findings, including dental anomalies, ectopic eruption of the maxillary permanent first molars and soft tissue alterations, in subjects with Apert syndrome. MATERIALS AND METHODS: clinical and radiographic examination of nine patients with Apert syndrome, aged 6 to 15 years, not previously submitted to orthodontic or orthognathic treatment. RESULTS: dental anomalies were present in all patients, with one to eight anomalies per individual. The most frequent anomalies were tooth agenesis, mainly affecting maxillary canines, and enamel opacities (44.4% for both). Ectopic eruption of maxillary first molars was found in 33.3% of patients; lateral palatal swellings were observed in 88.8% of patients. CONCLUSIONS: The occurrence of typical lateral palatal swellings agrees with the literature. The high prevalence of dental anomalies and ectopic eruption may suggest a possible etiologic relationship with the syndrome. INTRODUÇÃO: A síndrome de Apert é um distúrbio raro de herança autossômica dominante causado por mutações no lócus 10q26 do gene FGFR2; pacientes com esta síndrome apresentam sindactilia severa, exoftalmia, hiperteleorbitismo e hipoplasia da face média com má oclusão de Classe III, além de alterações sistêmicas. A maior parte dos estudos disponíveis sobre a síndrome de Apert aborda o aspecto genético ou manejo cirúrgico, com pouca ênfase nos aspectos bucais. OBJETIVO: investigar os achados bucais, incluindo anomalias dentárias, irrupção ectópica dos primeiros molares permanentes superiores e alterações de tecido mole, em indivíduos com síndrome de Apert. MATERIAIS E MÉTODOS: exame clínico e radiográfico de nove pacientes com síndrome de Apert, de 6 a 15 anos de idade, não anteriormente submetidos a tratamento ortodôntico ou ortognático. RESULTADOS: anomalias dentárias estavam presentes em todos os pacientes, com uma a oito anomalias por indivíduo. As anomalias mais freqüentes foram agenesia dentária, principalmente afetando os caninos superiores, e opacidades de esmalte (44,4% para ambos). Foi observada irrupção ectópica dos primeiros molares superiores em 33,3% dos pacientes; foram observados aumentos volumétricos laterais da mucosa palatina em 88,8% dos pacientes. CONCLUSÕES: a ocorrência de aumentos volumétricos laterais típicos da mucosa palatina concorda com a literatura. A alta prevalência de anomalias dentárias e irrupção ectópica pode sugerir uma possível relação etiológica com a síndrome.